Public Perception and Persuasive Verbal Communication of Audience Engagement at Consumer Exhibitions in Brunei Darussalam - Afifah Suhaili; Mas Ayu Mumin (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2024)
As Brunei Darussalam aims to promote a highly skilled and educated society, understandably effective verbal communication may play a crucial role in enhancing audience engagement and influence consumer behaviour in their purchasing decision. This research explored the impact of public perceptions and persuasive verbal communication towards audience engagement at consumer exhibitions in Brunei Darussalam. Through qualitative approach, the study employed a phenomenological design in gathering data through semi-structured interviews at the consumer exhibitions. The analysis revealed five themes: (1) interpersonal communication including friendliness, forcefulness and limited interaction, (2) promotional and interactive tactics were the important factors for exhibitors to consider to significantly enhance audience engagement. Moreover, public expected exhibitors to implement (3) informative language and product knowledge where they desired to receive clear and concise information about products or services offered. The key strategies that would contribute to audience engagement include (4) communication attributes where confidence, tone of voice, clarity and politeness must be practised by exhibitors and understanding the (5) influence of first impressions and branding including the perception of company values, word of mouth, visual design, credibility and persuasion. The findings provided insights into how persuasive verbal communication and audience engagement can be enhanced during consumer exhibitions, underscoring the need to adopt effective communication strategies that caters to the audience’s level of understanding and emotional comfort.